Global Transcriptome Analysis Revealed the Molecular Regulation Mechanism of Pigment and Reactive Oxygen Species Metabolism During the Stigma Development of Carya cathayensis - Xing, Yulin; Wang, Ketao; Huang, Chunying; Huang, Jianqin; Zhao, Yirui; Si, Xiaolin; Li, Yan (Frontiers in Plant Science, 2022)
Hickory (Carya cathayensis Sarg.) is a monoecious plant of genus Carya of the Juglandaceae family. Its nuts contain the amount of nutritional compounds and are deeply loved by consumers. Interestingly, it was observed that the color of hickory stigma changed obviously from blooming to mature. However, the molecular mechanism underlying color formation during stigma development and the biological significance of this phenomenon were mostly unknown. In this work, pigment content, reactive oxygen species (ROS) removal capacity and transcriptome analysis of developing stigma of hickory at 4 differential sampling time points (S1, S2, S3, and S4) were performed to reveal the dynamic changes of related pigment, antioxidant capacity and its internal molecular regulatory mechanism. It was found that total chlorophyll content was decreased slightly from S1 to S4, while total carotenoids content was increased from S1 to S3 but decreased gradually from S3 to S4. Total anthocyanin content continued to increase during the four periods of stigma development, reaching the highest level at the S4. Similarly, antioxidant capacity of stigma was also gradually improved from S1 to S4. Furthermore, transcriptome analysis of developing hickory stigma identified 31,027 genes. Time-series analysis of gene expressions showed that these genes were divided into 12 clusters. The cluster 5 was enriched with some genes responsible for porphyrin and chlorophyll metabolism, carotenoid metabolism and photosynthesis. Meanwhile, cluster 10 were enriched with genes related to flavonoid metabolism including anthocyanin involved in ROS scavenging, and its related genes were mainly distributed in cluster 12. Based on the selected threshold values, a total of 10432 differentially expressed genes were screened out and enriched in the chlorophyll, carotenoid, anthocyanin and ROS metabolism. The expression trends of these genes provided plausible explanations for the dynamic change of color and ROS level of hickory stigma with development. qRT-PCR analyses were basically consistent with the results of RNA-seq. The co-regulatory networks of pigment and ROS metabolism were further constructed and MYB113 (CCA0887S0030) and WRKY75 (CCA0573S0068) was predicted to be two core transcriptional regulators. These results provided in-depth evidence for revealing the molecular mechanism of color formation in hickory stigma and its biological significance.